PERENCANAAN PEMBELAJARAN DI SD TUNAS HARAPAN PATUMBAK (STUDI TENTANG POLA IDENTIFIKASI PERILAKU DAN KARAKTERISTIK AWAL PESERTA DIDIK) - Rahmat Rifai Lubis; Nur Fauziyah; Putri Maymuhamna Rahayu; Siti Hajar Hasibuan; Laras Utami (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2023)
Before deciding on a successful learning style to use in the classroom, teachers must first determine the fundamental features of their students. A teacher must be able to acknowledge the effectiveness of learning. During the learning process, teachers and students communicate with one another. Many educators still struggle to identify their students, which hinders the state of the learning process today. The learning process will be impacted by the student's preferred learning style, so the teacher needs to be aware of it. The teacher must create a lesson using the different learning preferences of each student in the class before the learning process can begin. It is crucial to work on improving instructor comprehension of this kind of student identification. A qualitative research methodology is the case study methodology. Peneliti mengandalkan masukan dari guru dan siswa. Penggunaan identifikasi ini mendorong pembelajaran yang efisien. Menurut temuan survei, mayoritas siswa kelas lebih menyukai pembelajaran auditori.